2023
DOI: 10.1017/dsj.2023.28
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence in design education: evaluating ChatGPT as a virtual colleague for post-graduate course development

Yaron Meron,
Yasemin Tekmen Araci

Abstract: This article explores the ability of ChatGPT to function as a virtual colleague in helping to design materials for higher education design students. Using a self-study methodology, two university educators attempted to collaborate with ChatGPT to create course materials targeted at higher education design students, before reflecting on its strengths and weaknesses during the process. Contextualising ChatGPT as the latest acute example of digital disruptors that design practices and processes have faced, the au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Such tools have the potential to revolutionize content creation, offering an excess of resources and interactive experiences that can support personalized learning paths (Fui-Hoon Nah et al, 2023). Furthermore, educators have found that when leveraged judiciously, ChatGPT can serve as a facilitator for idea generation and curriculum development (Meron & Araci, 2023), potentially enhancing the educator's role by automating administrative tasks and allowing for more focused pedagogical strategies. The dualistic nature of ChatGPT's impact-its prospective benefits shadowed by ethical and integrity-related quandariesunderscores the need for an in-depth examination of its role and regulation in educational settings.…”
Section: Introductionmentioning
confidence: 99%
“…Such tools have the potential to revolutionize content creation, offering an excess of resources and interactive experiences that can support personalized learning paths (Fui-Hoon Nah et al, 2023). Furthermore, educators have found that when leveraged judiciously, ChatGPT can serve as a facilitator for idea generation and curriculum development (Meron & Araci, 2023), potentially enhancing the educator's role by automating administrative tasks and allowing for more focused pedagogical strategies. The dualistic nature of ChatGPT's impact-its prospective benefits shadowed by ethical and integrity-related quandariesunderscores the need for an in-depth examination of its role and regulation in educational settings.…”
Section: Introductionmentioning
confidence: 99%
“…In previous works, opportunities and challenges of using ChatGPT have been discussed, with many providing a multidisciplinary view by analyzing contributions on both negative and positive aspects (Merón & Tekmen Araci, 2023). Regarding this, Dwivedi et al (2023) argue that the technology in question demonstrates improvements in productivity but also poses risks to security and privacy when used inappropriately.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding this, Dwivedi et al (2023) argue that the technology in question demonstrates improvements in productivity but also poses risks to security and privacy when used inappropriately. On the other hand, Merón and Tekmen Araci (2023), in examining the strengths and weaknesses of this application, consider it a potentially useful tool for designing materials; however, they also point out significant ethical limitations and challenges.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, researchers have used ChatGPT as an assistant for idea generation and data identification in finance research (Dowling & Lucey, 2023). As another example, ChatGPT has been used as a virtual colleague for developing postgraduate courses (Meron & Araci, 2023).…”
Section: Introductionmentioning
confidence: 99%